Big Macs and a three-legged stool: How innovation strategy drives McDonald's. Issue 5 (8th April 2014) - Unknown
Abstract : Purpose: – This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: – This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: – The case study and interview offers a unique insight into factors contributing to McDonald's unprecedented success (it has paid an increased dividend for the past 37 years). It also sheds light on its successful internationalization strategy. Practical implications: – The paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value: – The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.